HEART DISEASES MENTIONED IN QURAN AND THEIR SOLUTION: “A RESEARCH STUDY” - Muhammad Hassan Raza Nawaz; Zubair Munawar (Journal of Religion and Society, 2025)
The heart is the most vital organ of the human body, not only sustaining physical life but also serving as the center of spiritual and psychological existence. In the Qur'an, the significance of the heart is repeatedly emphasized, highlighting its role in shaping an individual's faith, morality, and overall spiritual well-being. The heart is portrayed as the seat of consciousness, the locus of divine guidance, and the vessel through which a person's sincerity and devotion to God are manifested. A sound heart is one that is filled with faith, humility, and righteousness, while a diseased heart is afflicted by moral and spiritual corruption. The concept of "cardiac diseases" in Islamic thought extends beyond physiological ailments to include moral and spiritual afflictions that affect an individual's thoughts, emotions, and actions. The Qur'an describes various spiritual diseases of the heart, such as misguidance, hypocrisy, arrogance, heedlessness, and hardness, which distance individuals from divine guidance and ethical conduct. A heart tainted by such diseases becomes incapable of perceiving truth, resisting guidance, and cultivating inner peace. Negligence and corruption of the heart lead to moral decay, social discord, and ultimately, a loss of connection with God. Conversely, the Qur'an highlights that a purified and enlightened heart is a prerequisite for attaining divine nearness and true success in this life and the Hereafter. The process of spiritual purification, known as tazkiyah, involves nurturing the heart with faith, sincerity, gratitude, and love for God, while guarding it against negative influences and desires. Reflection, prayer, and seeking divine knowledge are among the ways to soften the heart and restore its spiritual vitality. Ultimately, the state of the heart determines an individual's character, ethical conduct, and relationship with God, making it the focal point of both worldly and eternal well-being. Keywords: Heart Diseases in the Qur'an, Spiritual Ailments. Qur'anic Remedies for Heart Diseases, Purification of the Heart (Tazkiyah Al-Nafs), Righteousness (Taqwa) and Heart Health